The Effect of Crude Nipa Leaf Extract (Nypa fruticans) on the Quality and Shelf Life of Fresh Milkfish (Chanos chanos) - Ramadhani, Aji Fajar (EXSACT-A, 2024)
In the fishermen's environment, in general, fresh fish is preserved so that it does not spoil quickly by using ice, but the durability of ice is limited, so fishermen usually add formalin; formalin is generally used as a preservative for corpses and is prohibited from being added to food. Nipah leaf extract is very good to be used as an anti-bacterial compared to the fruit, so that it can be used as a natural preservative. This study aimed to determine the optimum concentration of the addition of crude nipa leaf extract on the quality of fresh milkfish. The sample in this study used milkfish preserved using nipa leaf extract as a natural preservative. This research was divided into two stages, namely, in the first stage, it was used to find the best concentration in making nipah leaf extract solution, and the second stage was carried out to determine the effectiveness of nipa leaf solution as a natural preservative. This study found that Nipah leaf extract with a concentration of 22.5% could increase the shelf life for 24 hours with a bacterial growth rate of 5.63±0.03 log cfu/g. This study concludes that Nipah leaf extract can inhibit decay in milkfish.Keywords— milkfish, nipah, anti-bacterial